The Dominance of the Ḥafṣ Qirāʾat: Its Impact on Qur’anic Recitation Across the Islamic World - Zakiyana Afazani Al Maula; Iffah Muzammil; Muhammad Habibulloh (Bulletin of Indonesian Islamic Studies, 2025)
The Ḥafṣ ʿan ʿĀṣim qirāʾa, one of the seven canonical readings in Islamic tradition, remains the most widely used recitation across the Muslim world, particularly in the Middle East, South Asia, Southeast Asia, and North Africa. This study examines the historical, political, and cultural factors behind its dominance and the implications for religious practice and Islamic education globally. Using a descriptive-analytical method based on literature review, the study finds that the spread of Ḥafṣ was reinforced by the codification of the Mushaf al-Madīnah in the twentieth century, which became the official standard in many Muslim-majority countries, supported by institutions and favored for its clarity of pronunciation. By contrast, other qirāʾāt such as Warsh ʿan Nāfiʿ have survived in parts of North Africa but have not achieved comparable reach. The findings show that the prominence of Ḥafṣ stems not only from textual features but also from publishing politics and educational policies. This study contributes a fresh perspective by highlighting the link between mushaf standardization and the marginalization of other qirāʾāt, thereby underscoring the importance of preserving recitational diversity as part of Islam’s intellectual heritage and as a resource for fostering intra-madhhab tolerance.